Anaesthetic management of a patient with severe aortic stenosis for caesarean section: a case report - Dsouza, Moses Charles; Shivappagoudar, Vikram M.; Kedlaya, Arpana; Gonsalvez, Gerard Joseph (International Journal of Research in Medical Sciences, 2017)
Aortic stenosis (AS) is an uncommon valvular heart disease presenting during pregnancy. Mild to moderate AS is associated with favorable pregnancy outcome but severe AS can worsen the hemodynamics during the peripartum period and precipitate heart failure, pulmonary edema, thus carrying significant maternal and fetal morbidity and mortality. Percutaneous balloon valvuloplasty can be used as a palliative procedure that allows for completion of pregnancy before definitive repair. We present a case of severe AS posted for caesarean section who was successfully managed under general anaesthesia and had an uneventful recovery.